Adaptasi Perusahaan Media Konvensional ke Era Digital: Studi Pada Radar Cirebon - Ujang Suryadi; Musahwi Musahwi; Nurlalili Khikmawati; Naila Farah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has encouraged mass media, especially print media, to transform in order to maintain its existence. This research aims to understand the adaptation process of Radar Cirebon Public Daily from print media to digital platform in facing the pressure of information disruption and changes in consumer behavior. Using a qualitative method with a case study approach, data was collected through in-depth interviews and content analysis on the Radar Cirebon digital platform. Everett Rogers' Diffusion of Innovation Theory was used to analyze the stages of innovation adoption as well as innovation characteristics that influenced the transformation process. The results showed that Radar Cirebon's adaptation took place gradually through five phases: knowledge, persuasion, decision, implementation, and reinforcement. In addition, this transformation involved changes in editorial work structure, organizational strategy, HR capacity building, and internal challenges in the form of cultural resistance.However, findings in the field also show a tendency for editors to produce processed content from online sources without direct coverage, raising critical questions regarding the loss of the essence of journalistic work and the shift in the role of editors to become mere SEO content producers. This research confirms that digital transformation requires not only technical adaptation, but also restructuring of work culture, professionalism values, and content innovation based on the needs of today's digital audience.